Amplification and function analysis of N6-adenine-specific DNA methyltransferase gene in Nilaparvata lugens - Jiao ZHANG; Yan-ru XING; Bo-feng HOU; Zhu-ting YUAN; Yao LI; Wen-cai JIE; Yang SUN; Fei LI (Journal of Integrative Agriculture, 2016)
Methylation of the N6 position of adenine, termed N6-methyladenine, protects DNA from restriction endonucleases via the host-specific restriction-modification system. N6-methyladenine was discovered and has been well studied in bacteria. N6-adenine-specific DNA methyltransferase (N6AMT) is the main enzyme catalyzing the methylation of the adenine base and knowledge of this enzyme was mainly derived from work in prokaryotic models. However, large-scale gene discovery at the genome level in many model organisms indicated that the N6AMT gene also exists in eukaryotes, such as humans, mice, fruit flies and plants. Here, we cloned a N6AMT gene from Nilaparvata lugens (Nlu-N6AMT) and amplified its full-length transcript. Then, we carried out a systematic investigation of N6AMT in 33 publically available insect genomes, indicating that all studied insects had N6AMT. Genomic structure analysis showed that insect N6AMT has short introns compared with the mammalian homologs. Domain and phylogenetic analysis indicated that insect N6AMT had a conserved N6-adenineMlase domain that is specific to catalyze the adenine methylation. Nlu-N6AMT was highly expressed in the adult female. We knocked down Nlu-N6AMT by feeding dsRNA from the second instar nymph to adult female, inducing retard development of adult female. In all, we provide the first genome-wide analysis of N6AMT in insects and presented the experimental evidence that N6AMT might have important functions in reproductive development and ovary maturation.